Comparative population genetic analysis of brackish- and freshwater populations of Eurasian perch (Perca fluviatilis L.): implication for fish forensics. - Lilian Pukk; Markus Vetemaa; Anti Vasemägi (Frontiers in Marine Science, 2015)
Understanding the genetic population structure of commercially important fish species is crucial for developing biologically sound management and conservation strategies. Genetic information can be also useful for fighting against illegal fishing and fish trade. Here, we studied commercially important brackish and freshwater populations of Eurasian perch (Perca fluviatilis L.) in Estonia, to describe the genetic divergence among populations and evaluate the power of 16 microsatellite markers to assign individual fish and group of fish to their population of origin. To do so, a total of 785 individuals caught from 13 different sites in the Baltic Sea and four locations in Lake Peipus were analyzed. We found significant differences in genetic diversity between brackish and freshwater populations with Baltic Sea samples showing slightly lower allelic richness and heterozygosity compared to Lake Peipus. We also observed moderate genetic differentiation among populations (overall FST=0.034). Individual self-assignment tests assigned large proportion of individuals correctly back to freshwater or coastal origin (Lake Peipus: 87.1%; Baltic Sea: 89.4%). Also, when evaluating the origin of group of individuals, it was possible to identify the origin of the brackish and freshwater fish groups with very high confidence (log 10 LR > 2) when sample size was larger than 15. Our results demonstrate the power of highly variable genetic markers separating two commercially most important Eurasian perch stocks in Estonia and the usefulness of assignment tests to successfully identify the genetic origin of fish.